2016
DOI: 10.1016/j.jhep.2016.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram variability in patients with cirrhosis associates with the presence and severity of hepatic encephalopathy

Abstract: Decreased variability or increased regularity of physiological systems is documented in several disease states. Variability of the electroencephalogram was found to be associated with both the presence and severity of brain dysfunction in patients with chronic liver disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…To the best of our knowledge these results are the first report, which make a link between the pattern of skin temperature fluctuations and the prognosis of patients within the context of chronic liver disease. These results also extend our knowledge about the potential application of physio-markers in the clinical assessment of patients with cirrhosis (Mani et al, 2009;Montagnese, De Rui, et al, 2015;Montagnese, Jackson, & Morgan, 2007;Olesen et al, 2016). There has been an interest in recent years in the application of HRV for monitoring patients with cirrhosis awaiting liver transplantation (Bhogal et al, 2019;Bhogal, Montagnese, & Mani, 2018;Chan, Yeh, & Sun, 2017;Jansen et al, 2019;Xiong, Faes, & Ch, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…To the best of our knowledge these results are the first report, which make a link between the pattern of skin temperature fluctuations and the prognosis of patients within the context of chronic liver disease. These results also extend our knowledge about the potential application of physio-markers in the clinical assessment of patients with cirrhosis (Mani et al, 2009;Montagnese, De Rui, et al, 2015;Montagnese, Jackson, & Morgan, 2007;Olesen et al, 2016). There has been an interest in recent years in the application of HRV for monitoring patients with cirrhosis awaiting liver transplantation (Bhogal et al, 2019;Bhogal, Montagnese, & Mani, 2018;Chan, Yeh, & Sun, 2017;Jansen et al, 2019;Xiong, Faes, & Ch, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…No association was observed between the aetiology of liver disease and functional EEG connectivity parameters. This contrast with a previous EEG study which showed an increase in beta activity in patients with alcohol-related cirrhosis, possibly reflecting changes in gamma aminobutyric acid (GABA) neurotransmission (Olesen et al, 2016). Variations in the GABA alpha-2 gene are strongly associated with the beta frequency of the human EEG and genetic studies have provided evidence of involvement of the GABA system in the susceptibility to develop alcohol dependence through an effect on neural excitability (Lydall et al, 2011;Saletu-Zyhlarz et al, 2004).…”
Section: Functional Connectivity and The Severity And Aetiology Of The Liver Diseasementioning
confidence: 72%
“…230 In recent studies, the decrease in EEG amplitude in patients with OHE was associated with the severity of HE. 231 The brainstem auditory-evoked-potential test is sensitive for the diagnosis of CHE. 226,227,232 Patients with liver cirrhosis accompanied by CHE exhibit conduction time delays (I-V latency) from the auditory nerve to the midbrain and conduction time delays (III-V latency) from the pontine to the midbrain on the brain auditoryevoked-potential test.…”
Section: Differential Diagnosismentioning
confidence: 99%